2015
DOI: 10.1111/1541-4337.12152
|View full text |Cite
|
Sign up to set email alerts
|

Mealiness Detection in Agricultural Crops: Destructive and Nondestructive Tests: A Review

Abstract: Mealiness is known as an important internal quality attribute of fruits/vegetables, which has significant influence on consumer purchasing decisions. Mealiness has been a topic of research interest over the past several decades. A number of destructive and nondestructive techniques are introduced for mealiness detection. Nondestructive methods are more interesting because they are rapid, noninvasive, and suitable for real-time purposes. In this review, the concept of mealiness is presented for potato, apple, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 130 publications
(218 reference statements)
0
16
0
Order By: Relevance
“…There is a lack of data on the effect of tomato grafting on flesh mealiness , as assessed by trained panels. In the literature, much attention has been given to understanding the basis and development of mealiness and many questions still need to be answered ( Crisosto and Labavitch, 2002 ; Devaux et al, 2005 ; Toivonen and Brummell, 2008 ; Arefi et al, 2015 ). Fruit mealy texture is most likely caused by cell separation instead of cell rupture ( Arefi et al, 2015 ), as indicated by the high correlation of mealiness and the number of fragments and cells produced ( Devaux et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a lack of data on the effect of tomato grafting on flesh mealiness , as assessed by trained panels. In the literature, much attention has been given to understanding the basis and development of mealiness and many questions still need to be answered ( Crisosto and Labavitch, 2002 ; Devaux et al, 2005 ; Toivonen and Brummell, 2008 ; Arefi et al, 2015 ). Fruit mealy texture is most likely caused by cell separation instead of cell rupture ( Arefi et al, 2015 ), as indicated by the high correlation of mealiness and the number of fragments and cells produced ( Devaux et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, much attention has been given to understanding the basis and development of mealiness and many questions still need to be answered ( Crisosto and Labavitch, 2002 ; Devaux et al, 2005 ; Toivonen and Brummell, 2008 ; Arefi et al, 2015 ). Fruit mealy texture is most likely caused by cell separation instead of cell rupture ( Arefi et al, 2015 ), as indicated by the high correlation of mealiness and the number of fragments and cells produced ( Devaux et al, 2005 ). Fruit mealy texture is negatively correlated with protein and uronic acid content and positively correlated with pectin content ( Brownleader et al, 1999 ; Devaux et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maturity indices can be obtained via destructive and nondestructive methods and take into account chemical composition (e.g., total acidity), physical properties [e.g., firmness (Zhang et al 2008)], fruit physiological changes [e.g., ethylene emission rate (Kathirvelan and Vijayaraghavan 2017)], and chronological features [e.g., days after blooming (Knee 2002)]. Destructive methods are methods which the fruits or vegetable are subject to a test that degrades, e.g., penetration, compression, the product leaving it not consumable, while non-destructive methods use remote sensing techniques, e.g., acoustic impulse response, near-infrared (Arefi et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…[1] However, some drawbacks including being destructive and time-consuming limited its application for online monitoring of mealiness. To overcome these problems, non-destructive assessment of mealiness in apples has been investigated using ultrasonic [5] , nuclear magnetic resonance\magnetic resonance imaging [6,7] , near-infrared spectroscopy [8] , chlorophyll fluorescence [3,9] , hyperspectral scattering imaging [4,10] , and laser-light backscattering imaging [11] which a comprehensive review of them is given in Arefi et al [12] Currently efforts are still being continued to achieve mealiness detection systems of better performance in terms of accuracy, time, and cost.…”
Section: Introductionmentioning
confidence: 99%